From Urbanization to Metropolization: A Conceptual Approach - Gonçalves, Tiago Estevam; Silva, José Borzacchiello da; Araújo, Enos Feitosa de (Sociedade & Natureza, 2024)
The article approaches the processes of metropolization with regard to urban development and spatial organization of the city in their continuous and articulated processes. The perspective of this analysis is that there is a new basis for urban/metropolitan dynamics, moving out from an industrial and post-Fordist economy to a financialization of the economy, which we call metropolization. From the recent dynamics of the concentration of people and the expansion of urban space, some discussions can emerge about the new socio-spatial reality. Concerning metropolization, our main objective is to discuss the concept of urbanization and metropolization, aiming to understand the spatial transformations of the contemporary world. In methodological terms, we sought a bibliographic survey on the dialogical relationship between urbanization and metropolization with Brazilian and foreign authors who are relevant in the Brazilian academic literature and, in turn, are present in the urban/metropolitan analysis. The presence of temporal, economic and spatial dimensions has been deemed the main drivers for metropolization. As a result, the concept of metropolization was understood as a socio-spatial process that interferes in the forms, functions and dynamics of large urban spaces, and that has been acquiring importance in the context of the contemporary world, being a characteristic that pervades urbanization, reaching both countries in the global South as in the global North.